Serine racemase deletion disrupts memory for order and alters cortical dendritic morphology - DeVito, Loren M. (2010)
There is substantial evidence implicating N-methyl-d-aspartate receptors (NMDARs) in memory and cognition. It has also been suggested that NMDAR hypofunction might underlie the cognitive deficits observed in schizophrenia since morphological changes, including alterations in the dendritic architecture of pyramidal neurons in the prefrontal cortex (PFC), have been reported in the schizophrenic brain post mortem. Here, we used a genetic model of NMDAR hypofunction, a serine racemase knockout (SR−/−) mouse in which the first coding exon of the mouse serine racemase gene has been deleted, to explore the role of d-serine in regulating cognitive functions as well as dendritic architecture. SR −/− mice exhibited a significantly disrupted representation of the order of events in distinct experiences as revealed by object recognition and odor sequence tests; however, SR −/− animals were unimpaired in the detection of novel objects and in spatial displacement, and showed intact relational memory in a test of transitive inference. In addition, SR −/− mice exhibited normal sociability and preference for social novelty. Neurons in the medial PFC of SR−/− mice displayed reductions in the complexity, total length, and spine density of apical dendrites. These findings demonstrate that d-serine is important for specific aspects of cognition, as well as in regulating dendritic morphology of pyramidal neurons in the mPFC. Moreover, they suggest that NMDAR hypofunction might, in part, be responsible for the cognitive deficits and synaptic changes associated with schizophrenia, and highlight this signaling pathway as a potential target for therapeutic intervention.